El poema del Mío Cid - Reyna Guevara, Jose Antonio (2019)
The present work has been made out for students in the fifth grade, secondary education in the year 2019 with the theme entitled "The Poem of Mine Cid", in this session has had himself in account that students analyze and know the contents of the poem where they consist of three Song: Singing of Exile, Song of the Weddings and Song of the Corpes affront. In the elaboration of the session he has been worked up with the pedagogic, psychological processes that every student to achieve your significant learning should take into account. The used strategies were designed for promoting the students' active and significant participation. The learning session will be evaluated through a questionnaire of questions and he orchestrated a closing to evaluate the development of the competition.